An integrated scheduling genetic algorithm based on process constraint matrix and family definition coding - Qian, Chao; Zhang, Jianxin (Journal of physics. Conference series, 2025)
To address the complex product-integrated scheduling problem, an improved genetic algorithm based on process constraint matrix and family definition is proposed. The algorithm features a coding method that accurately represents the processing sequence constraints in the product process tree and introduces a simplified method for defining families and sub-processes. On this basis, a hierarchical relationship matrix is derived from the constraint matrix. To resolve the issue of infeasible solutions arising from crossover and mutation operations, a family-based single-parent genetic improvement algorithm is designed. Experimental results validate the effectiveness of the proposed algorithm.